Breast cancer in men. A case report - M. V. Kiseleva; S. A. Ivanov; M. N. Lunkova; I. A. Zharikova; M. S. Denisov; E. V. Litvyakova (ABV-press, 2022)
Malignant breast tumors in men are quite rare and require deeper investigation. Men are 100 times less likely to develop breast cancer than women. However, its incidence among men has grown over the last few years. In this article, we describe own observations of breast cancer in males and report a case of ст1сN0M0 stage 1A cancer of the left breast in a man and provide the details of clinical and morphological disease characteristics, tumor immunohistochemistry, and treatment outcome.